Sobre la naturaleza de la investigación proyectual (2004)
The following essay concludes the reflections made since 1988 upon the architectís concern for the way in which he/she produces knowledge and does research through the architectural project. The projectation processes as research logic appear within the professional and teaching fields of our local and national milieu as a suggestive and novel idea, that deserves to be debated. The questions to this respect are approached focusing upon the relation between the architect and the architectural object, and between project and research, as well as the production of architectural knowledge.